Research and Application Progress of Downhole Gas-Liquid Separation Technology - Gao, Sheng; Gao, Borui; Zou, Fabao; Huang, Pingchao; Yang, Lu (Journal of Research in Science and Engineering, 2025)
With the continuous advancement of oil and gas field development, the problem of water production in gas wells has become increasingly prominent, severely affecting natural gas production efficiency and economic benefits. As an effective solution, downhole gas-liquid separation technology can achieve gas-liquid separation in the wellbore, reinjecting water-rich fluids into the formation and lifting gas-rich fluids to the surface. This reduces lifting and treatment costs, minimizes environmental pollution, and improves recovery efficiency. This paper elaborates on the research and application progress of downhole gas-liquid separation technology, including its technical principles, main equipment, application cases, and future development trends, aiming to provide references for the further development and promotion of this technology.